Keabsahan Saksi Istifadhah dalam Perkara Istbat Nikah di Pengadilan Agama Barabai Kelas IB Kabupaten Hulu Sungai Tengah Provinsi Kalimantan Selatan (Studi Kasus Penetapan Nomor 211/Pdt.P/2023/PA.Brb) - Ardila, Titi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
This research examines the validity of using istifadhah witnesses (witnesses based on public hearsay) in marriage legalization cases at the Barabai Religious Court. The primary legal issue arises when the witnesses presented in court did not personally witness the marriage contract (de auditu), whereas Article 171 of the HIR (Indonesian Procedural Law) requires witnesses to have direct knowledge. However, in Decree Number 211/Pdt.P/2023/PA.Brb, the Sole Judge accepted and declared such witness testimony as valid. This study aims to determine the legal basis and Islamic jurisprudence (fiqh) rules used by the judge and to analyze the judge's legal reasoning in constructing the validity of istifadhah witnesses to reach a legal conviction. This is a field research with a socio-legal approach. Primary data were obtained through an analysis of the court decree and in-depth interviews with the Sole Judge at the Barabai Religious Court. The data were analyzed qualitatively using descriptive-analytical methods, supported by evidence theory and substantive justice theory. The results show that: 1) The validity of istifadhah witnesses in this case is based on the integration of the Supreme Court Circular (SEMA) Number 10 of 2020 as formal legality and the Book of I’anatut Thalibin, as well as the fiqh maxim "Dar’ul mafasid muqaddamun ‘ala jalbil mashalih" (averting harm takes precedence over acquiring benefits) as the philosophical foundation. 2) The judge constructed the validity of the witnesses through a legal presumption method due to the emergency of evidence (adh-dharurah) caused by the long duration of the marriage (45 years). The witness testimony was deemed valid and possessed perfect evidentiary strength (volledig bewijs) because it met the element of public notoriety (syuhrah) and was consistent with other evidence, thereby providing legal certainty and substantive justice for the Petitioners.